Risk factors for necrotizing enterocolitis in neonates: A meta-analysis - Su, Yan; Xu, Rui-Hong; Guo, Li-Yan; Chen, Xin-Qing; Han, Wen-Xiao; Ma, Jin-Jin; Liang, Jiao-Jiao; Hao, Ling; Ren, Chang-Jun (Frontiers in Pediatrics, 2023)
Objective The objective is to identify the risk factors for necrotizing enterocolitis (NEC) in neonates by a meta-analysis, and to provide a reference for the prevention of NEC. Methods The databases, including Chinese Biomedical Literature Datebase, China National Knowledge Infrastructure, Wanfang database, and Weipu Periodical database, PubMed, Web of Science, Embase, Cochrane Library, were searched for studies on the risk factors for NEC in neonates. The meta-analysis was carried out with the aid of Stata software. Results A total of 52 studies were included, with 48 case-control studies and 4 cohort studies. There were 166,580 neonates in total, with 33,522 neonates in the case group and 133,058 neonates in the control group. The meta-analysis showed that gestational diabetes (OR = 3.62, 95% CI:1.77–7.41), premature rupture of membranes (OR = 3.81, 95% CI:1.16–12.52), low birth weight (OR = 3.00, 95% CI:2.26–3.97), small for gestational age (OR = 1.85, 95% CI:1.15–2.97), septicemia (OR = 4.34, 95% CI:3.06–6.15), blood transfusion (OR = 3.08, 95% CI:2.16–4.38), congenital heart disease (OR = 2.73, 95% CI:1.10–6.78), respiratory distress syndrome (OR = 2.12, 95% CI:1.24–3.63), premature birth (OR = 5.63, 95% CI:2.91–10.92), pneumonia (OR = 4.07, 95% CI:2.84–5.82) were risk factors for NEC in neonates. Breastfeeding (OR = 0.37, 95% CI:0.23–0.59), take probiotics (OR = 0.30, 95% CI:0.22–0.40), prenatal use of glucocorticoids (OR = 0.39, 95% CI:0.30–0.50), Hyperbilirubinemia (OR = 0.28, 95% CI:0.09–0.86) were protective factors for NEC in neonates. Conclusions Gestational diabetes, premature rupture of membranes, low birth weight, small for gestational age, septicemia, blood transfusion, congenital heart disease, respiratory distress syndrome, premature birth, and pneumonia may increase the risk of NEC in neonates. Breastfeeding, taking probiotics, prenatal use of glucocorticoids, and Hyperbilirubinemia may reduce the risk of NEC in neonates.